Sistema microemulsionado: caracterização e aplicação na indústria de petróleo - Silva, Guymmann Clay da (2011)
Alkyl polyethoxylates are surfactants widely used in vastly different fields, from oil exploitation to pharmaceutical applications. One of the most interesting characteristics of these surfactants is their ability to form micellar systems with specific geometry, the so-called wormlike micelle. In this work, microemulsions with three distinct compositions (C/T = 40 %, 30 % and 25 %) was used with contain UNITOL / butanol / water / xylene, cosurfactant / surfactante (C/S) ratio equal to 0,5. The microemulsion was characterized by dynamic light scattering (DLS), capillary viscometry, torque rheometry and surface tensiometry experiments carried out with systems based on xylene, water, butanol (cosurfactant) and nonaethyleneglycolmonododecyl ether (surfactant), with fixed surfactant:cosurfactant:oil composition (with and without oil phase) and varying the overall concentration of the microemulsion. The results showed that a transition from wormlike micelles to nanodrops was characterized by maximum relative viscosity (depending on how relative viscosity was defined), which was connected to maximum effective diameter, determined by DLS. Surface tension suggested that adsorption at the air water interface had a Langmuir character and that the limiting value of the surfactant surface excess was independent of the presence of cosurfactant and xylene. The results of the solubilization of oil sludge and oil recovery with the microemulsion: C/S = 40%, 30% and 25% proved to be quite effective in solubilization of oil sludge, with the percentage of solubilization (%solubilization) as high as 92.37% and enhanced oil recovery rates up to 90.22% for the point with the highest concentration of active material (surfactant), that is, 40%.